Delayed diagnosis of active pulmonary tuberculosis - Santos, João Almeida (2021)
Funding Information: Fundação para a Ciência e Tecnologia provided financial support to conduct this research [Grant: PTDC/SAU-PUB/31346/2017]. Publisher Copyright: © 2021, The Author(s).